THE INFLUENCE OF THE HYPNOTEACHING METHOD ON THE ABILITY TO RECOGNIZE ENGLISH IN CHILDREN AGED 5-6 YEARS AT RA AKMALA SABILA - Sopiah, Cucu Sopiah; Hijri, Rina; Nisa, Puja Adzka (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
A B S T R A K English learning as a foreign language is often considered difficult by young children, leading to a lack of interest in learning. This prompted the use of the hypnoteaching method to address the issue. This study aims to determine the effect of the hypnoteaching method on the English recognition skills of children aged 5-6 years at RA Akmala Sabila. The research employed a quantitative Pre-Experimental One Group Pretest-Posttest Design with a sample of 17 children from group B1. The results of the Paired Sample T-Test showed a sig. value of 0.000 (less than α 0.05), indicating that Ha is accepted. The pretest mean score was 33.24, and the posttest mean score was 57.65, demonstrating a significant improvement in English skills after applying the hypnoteaching method